TEACHING SPEAKING THROUGH STORYTELLING - Rahmawati, Istiqomah Nur (2014)
The objective of this study entitled 'Teaching Speaking through Storytelling' was to find out whether or not storytelling technique was effective to improve the students' speaking skill and to find out the students' responses towards the implementation of teaching speaking through storytelling. This study used a quantitative analysis method by using a pre experimental design. The population of the study was the students of a university in Bandar Lampung. The sample of the study was the first semester students of English Education. The data used in this study were the class observation data, speaking test and questionnaires given to the experimental group. To answer the first research problem, the data from speaking test were analyzed using t-test. The result showed that there was significance difference between the mean of pre-test and post-test, whereas the mean of post-test (91.15) was higher than the mean of pre-test (59.33). This means that the use of storytelling was effective in improving students' speaking ability. The second research problem was answered by the data from questionnaires. The data showed that, in general, students give positive responses toward teaching speaking through storytelling. Therefore, it is suggested that the lecturers implement storytelling as one of techniques in teaching English, specifically in speaking class since it gives benefits to the students' English skill and performance. It is expected that lecturers when they implement this technique should be more creative in finding story for the students to attract their attention and interests in teaching learning process. It will be better if the story is the local one with good values. Second, it is recommended that the lecturers use storytelling technique not only in speaking class but also in another class such as listening, reading, or writing. They can apply the technique and modify the teaching learning process based on their teaching styles. Then, as for further study, the future researchers are suggested to conduct further study using storytelling technique. Some possibilities may be more comprehensive for the future study in terms of level of classes, duration of time, and the use of other techniques to compare.